Human Rights in Judaism and the Jewish Legal Tradition - A. V. Krylov; A. V. Fedorchenko (Vestnik MGIMO-Universiteta)
Book Review: V.P. Vorobev, R.L. Iliev. Human Rights in Judaism and the Jewish Legal Tradition. Moscow: “Nazionalnoe Obozrenie” Publ. House, 2018. 248 p. (In Russian).V.P. Vorobiev and R.L. Iliev analyse the causes associated with the emergence of the concept of human rights and its understanding, referring to Judaism, which largely identified the modern definition of «human rights». The publication will be useful for all those interested in human rights issues.